Variant Analysis of the Ownership Structure of Land Intended for Single-family Housing - Jasińska, Elżbieta; Hanus, Paweł; Maciejko, Alicja; Skiba, Marta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The most frequently preferred solution for the ownership structure of land for single-family housing in Poland is the structure of one cadastral plot - one single-family building. However, changing architectural concepts allow for the creation of single-family housing estates in systems consisting of atrial houses or T-type buildings, which have much more advantages than traditional terraced or semi-detached buildings.
Keywords: land ownership; single-family housing; T-houses; Atrium houses; cadastre; architecture